Influences of the Kuroshio on the salinity budget of the Seto Inland Sea, Japan - Matsuda Kazuki; Uchiyama Yusuke (E3S Web of Conferences)
The Seto Inland Sea (SIS) harbors abundant aquatic biological diversity, while its ecosystem has been affected by climate change in recent years. Previous studies have shown that the residual current in the SIS varies significantly under the influence of the Kuroshio. To isolate the open ocean influences, salinity transport and the associated salinity budget in the SIS were investigated, as a conservative variable characterizing the estuarine hydrodynamics, using a high-resolution, long-term 3D circulation model. Our findings indicate that the fluctuations of salinity fluxes were influenced by the position of the Kuroshio axis and were highly correlated with the associated volume fluxes. The clockwise eastward transport from Bungo to Kii varies seasonally with an increase in winter and a decrease or counterclockwise increase in summer. The total salinity in each of the eight sub-basins of the SIS was also correlated with the salinity fluxes at the straits connecting the sub-basins. The total salinity in the western sub-basins increased with the eastward clockwise transport and decreased with the westward counterclockwise transport, whereas the eastern sub-basins showed less correlations, resulting in a zonal difference of salinity response to the open ocean.